Strategi Manajemen Konflik Berbasis Nilai Islam dalam Peningkatan Kinerja Guru - Maftuhah Nurmalika Febrianti; Hamidatul Afifati Fauziah; Mukhlishah AM; Mardiyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This research is motivated by the importance of conflict management as a process of planning and implementing strategies aimed at controlling conflict to produce the desired resolution. In its implementation, conflict management is designed by adopting the management functions of planning, organizing, actuating, and controlling (POAC), which directly support the improvement of teacher performance. This study aims to determine conflict management strategies in improving teacher performance at MTsN 1 Sumenep. This study uses a qualitative approach with a case study type, utilizing data collection techniques through in-depth interviews, participant observation, and documentation studies. The results of this study reveal that the conflict management strategies implemented at MTsN 1 Sumenep are based on theology from the Qur'an and Hadith, including: 1) negotiation; 2) tabayyun; 3) deliberation; 4) tahkim; and 5) islah. The implications of these findings confirm that effective conflict management can be carried out to improve teacher performance based on Islamic values.